Sediment Transport Analysis at Pantai Perpat, Batu Pahat, Johor - Suhaimi, Nor Izzati Shafina; Che Rahim, Muhammad Syakir Danial; Abd Rahman, Muhammad Hidayat Azhari; Hamid, Nor Baizura (Multidisciplinary Applied Research and Innovation, 2024)
Environmental problems are a big deal in coastal areas, especially those that are closely related to sedimentation. This problem may be increase the concentration of sediment, and change the quality of the water. The goal of this study was to evaluate the suspended sediment content, water quality, and influencing shoreline changes and sediment deposition in Pantai Perpat, Johor. The laboratory tests on water samples are pH and temperature, turbidity, and total suspended solids test while tests on sediment samples are sieve analysis, specific gravity, and moisture content test. The questionnaire was conducted through the medium of Google Forms, which is to find out the cause of sedimentation in the study area. First objective was achieved using a sieve analysis test. Results show that medium and low tide samples for Zone 1, Zone 3, and Zone 4 are well-graded soil. The result for the specific gravity test was 2 for all zones except Zone 2. The specific gravity of soils is in the range of 2.60 to about 2.80. For the moisture content testing result, high tide in Zone 1 contains 28.86% compared to medium tide with a value of 105.02% and low tide with 123.75%.. Then, for the water test, the pH result was 7, which is an alkaline state, with an average value of total suspended solids of 699 NTU and an average value of turbidity of 11400 mg/L. This shows that as the turbidity value increases, the total suspended solid (TSS) also increases. By 50 respondents, 56.7% said that the causes of increased sand deposition are affected by currents and waves; 28.4% said it was blown by coastal tides; and 14.9% said it was blown by monsoon winds and coastal winds. In conclusion, all the results obtained answered all the objectives, and this study was successful.